Developing Program Code for Automatic Color Code Sensing Punching Machine Using WPL Software (International Journal of Innovative Research in Engineering & Management, 2022)
This paper presents the idea of developing  a logic or program code for an Automatic Color code  sensing and punching machine which is driven based on  Pneumatic architecture and can be used at the packing  section in industries where the end user can punch labels  on the objects which are moving on the conveyor based on  their color. The program code basically controls the  Pneumatic valves present in the system which actuates the  Cylinders and helps in clamping and de clamping of  moving objects and henceforth achieving the label at  required spot, whereas the desired color is acquired from  the dedicated color sensor which helps in deciding the  labeling process.  This paper uses the advanced industrial controller (PLC)  software called WPL Soft which is the most widely used  tool in industries. This software requires a dedicated  programming language called Ladder diagram, which is  the 80% preferred programming language worldwide for  programming PLCs. A program has been developed for  automatically creating the application for color sensing  and punching label on the desired objects based on color.
Keywords: Developing Program; Automatic Color; Punching Machine